2019
DOI: 10.1002/lary.27987
|View full text |Cite
|
Sign up to set email alerts
|

Does drug‐induced sleep endoscopy affect surgical outcome? A multicenter study of 326 obstructive sleep apnea patients

Abstract: Objectives/Hypothesis Our objective was to determine whether drug‐induced sleep apnea (DISE) affects the successfulness of the surgical outcome. Study Design Prospective, seven‐country, nonrandomized trial. Methods There were 326 consecutive obstructive sleep apnea (OSA) patients who had nose, palate, and/or tongue surgery included in the study. DISE was performed in only one group. Results There were 170 patients in the DISE group and 156 patients in no‐DISE group. The mean preoperative body mass index (BMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…DISE evaluates the specific site and character of the upper airway obstruction during a pharmacological sleep. Although some studies have indicated a higher surgical success rate after DISE 53 , there is insufficient evidence to claim that this approach leads to a better surgical outcome compared to a normal clinical evaluation of the upper airway in fully awake patients 54,55 .…”
Section: Surgerymentioning
confidence: 99%
“…DISE evaluates the specific site and character of the upper airway obstruction during a pharmacological sleep. Although some studies have indicated a higher surgical success rate after DISE 53 , there is insufficient evidence to claim that this approach leads to a better surgical outcome compared to a normal clinical evaluation of the upper airway in fully awake patients 54,55 .…”
Section: Surgerymentioning
confidence: 99%
“…Some studies have reported that DISE-based diagnosis increases the success rates of sleep surgery [24,25]. In a multicenter study on OSA patients with single-or multi-level occlusion, the surgical outcome of DISE was significantly worse than that of MM [26]. However, most of these previous studies compared the surgical outcomes based on MM and DISE, with respect to UPPP (including [2]; AHI < 10/h with ≥50% AHI improvement [3]; ≥50% AHI improvement.…”
Section: Discussionmentioning
confidence: 96%
“…However, selection bias was introduced by collecting more patients with deviated nasal septum in the non-DISE group. The treatment methods differ among tertiary referral centers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%